2006
DOI: 10.1007/s10035-006-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Granular gases in mechanical engineering: on the origin of heterogeneous ultrasonic shot peening

Abstract: The behavior of an ultrasonic shot peening process is observed and analyzed by using a model of inelastic hard spheres in a gravitational field that are fluidized by a vibrating bottom wall (sonotrode) in a cylindrical chamber. A marked heterogeneous distribution of impacts appears when the collision between the shot and the side wall becomes inelastic with constant dissipation. This effect is one order of magnitude larger than the simple heterogeneity arising from boundary collision on the cylinder. Variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The hardness measurements indicate strong work-hardening and plastic strains near the surface of the sample. Other authors [14,28,29] also observed grain refinement and hardness increasing (depending of treatment's time and parameters). Zhu et al [14] have studied the microstructure at different depth after SMAT treatment.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The hardness measurements indicate strong work-hardening and plastic strains near the surface of the sample. Other authors [14,28,29] also observed grain refinement and hardness increasing (depending of treatment's time and parameters). Zhu et al [14] have studied the microstructure at different depth after SMAT treatment.…”
Section: Discussionmentioning
confidence: 80%
“…This method consists of vibrating WC balls in a closed chamber using high-power ultrasound (20 kHz of frequency). The balls projected on the sample surface induce large residual compressive stresses, strong plastic strains, and a nano-structuration of the sub-surface of the material [14,15]. The height of the chamber is 15 mm and the amplitude of vibration during the treatment is 12 lm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tangential coefficient is considered to be constant with a value of 5/7 [15,16]. The normal coefficients (C 0 i , i = {SHOT, WALL, BOT, TOP}), however, follow the power law given below; according to phenomenological models [16] and experiments [17]:…”
Section: Symbolsmentioning
confidence: 99%
“…Under the peening chamber, a titanium sonotrode is placed, and on top of the chamber aluminum sample. The restitution coefficients [17,18], as well as the process parameters, chosen for running the calculations, are listed in Table 1. The extracted data from each calculation correspond to a peening time of 30 s. In terms of impact on the sample, this corresponds to 17 434; 35 088 and 67 812 impacts respectively for the 5 g, 10 g and 20 g amounts.…”
Section: Symbolsmentioning
confidence: 99%